Incontinentia Pigmenti (IP) in Late Preterm Infant - Alghriani, Deiaeddin; TANTOUSH, ABDULMUEZ (Khalij-Libya Journal of Dental and Medical Research, 2026)
Incontinentia pigmenti (IP) is a rare X‑linked dominant neurocutaneous disorder that predominantly affects females and is often lethal in males. It is caused by mutations in the IKBKG (NEMO) gene, leading to dysregulation of NF‑κB signalling and multisystem involvement. We report the case of a female infant born preterm at 34+6 weeks to a mother with type 2 diabetes and hypothyroidism. The infant presented at birth with vesiculobullous skin lesions that evolved into pustular and crusted eruptions along Blaschko lines, consistent with IP. A family history revealed two older sisters with similar cutaneous findings in later stages, strengthening diagnostic suspicion. The neonatal course was complicated by hypoglycaemia requiring intensive glucose therapy and subsequent hypernatremic dehydration managed with careful fluid balance. Empirical antibiotics were initiated for presumed sepsis but discontinued after negative cultures. Dermatology review, genetic counselling, and multidisciplinary follow‑up were arranged. This case highlights the diagnostic challenges of early IP presentations, which may mimic neonatal infection, and underscores the importance of recognising Blaschko line distribution and eliciting family history. Vigilant monitoring for metabolic disturbances and systemic complications, alongside coordinated multidisciplinary care, is essential to optimise outcomes in affected neonates.